Entre vivências e lembranças de uma Comunidade Quilombola: história, memória e discurso - Elisângela de Jesus Furtado da Silva (2019)
This work deals with history, memory and social organization and is aimed at building a possible version of history. The problem of research is what stories can be constructed discursively from the memories of women in the community. Its purpose was to analyze the way in which the history of the Luizes community can be built from the memory of its members. The specific objectives are to: i) identify the main memories of elderly women of Quilombo Luizes about the community, which was done through unstructured interviews as a Oral History technique; ii) organize and analyze shared collective memories through the discursive historical approach proposed by Wodak (2001a) and iii) articulate the memories and analyzes to the possible stories of the Luizes community. The work was based on the nominalist ontology, based on the inductive method, being the qualitative research. The Luizes community is located in the Grajaú neighborhood, western region of Belo Horizonte. From the re-reading of the data, it was possible to identify two major prevailing discourses in the narrative of the interviews about their memories. They relate to issues of the community and other social groups, that is, the narratives were based on factors that, ultimately, are responsible for deferring the community from other social groups. Thus, we have the origin of two discursive macrotópicos identified in the data. The first macrotopic was named This whole complex Luizes, composed of subtopics, which refer to the stories about: a) self- identification; b) social organization; c) subsistence; d) work; e) gender; f) generation, g) resistance and h) religion. The second macrotopic refers to "The Others": a) Grajaú neighborhood stories; b) stories of support institutions and government; and c) stories of educational institutions, all of which interface with the Luizes Community. These subtopics are approached from the lexicons and excerpts extracted from the narratives. The results obtained from the interviewees' memories allow us to tell several stories of the Luizes Community, which refer to the dynamics of the group and of it as other social groups, which indicates that the stories and memories can be associated with a discourse of identity. That is, the narratives were based on factors that, ultimately, are responsible for deferring the community from other social groups.